2017
DOI: 10.1038/gim.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

The significant impact of education, poverty, and race on Internet-based research participant engagement

Abstract: PurposeInternet-based technologies are increasingly being utilized for research studies. However, it is not known whether using internet-based approaches will effectively engage participants from diverse racial and socioeconomic backgrounds.Methods967 participants were recruited and offered genetic ancestry results. We evaluated viewing internet-based genetic ancestry results among participants who expressed high interest in obtaining the results.Results64% of participants stated that they were very or extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In this analysis of observational study and clinical trial participants, race did not persist after multivariate analysis as an influential factor for high reported interest in receiving genetic susceptibility testing results. In a similar study evaluating smokers’ desire to view genetic ancestry results among 924 participants from this same observational study, there was also no significant difference between African-American and Caucasian interest in viewing results; African-American participants, however, demonstrated lower engagement in actually viewing their results online (Hartz et al 2016). This may be related to issues of access, which are equalized in this current study as genetic testing was provided free of charge and susceptibility results were not disclosed to participants.…”
Section: Discussionmentioning
confidence: 92%
“…In this analysis of observational study and clinical trial participants, race did not persist after multivariate analysis as an influential factor for high reported interest in receiving genetic susceptibility testing results. In a similar study evaluating smokers’ desire to view genetic ancestry results among 924 participants from this same observational study, there was also no significant difference between African-American and Caucasian interest in viewing results; African-American participants, however, demonstrated lower engagement in actually viewing their results online (Hartz et al 2016). This may be related to issues of access, which are equalized in this current study as genetic testing was provided free of charge and susceptibility results were not disclosed to participants.…”
Section: Discussionmentioning
confidence: 92%
“…In prior work, African Americans, regardless of socioeconomic status, were less likely to access study results in a genetic study of smoking, even after they previously indicated interest in receiving the results. 26 Policies and practices related to return of information must recognize these differences and use culturally appropriate messaging as well as avoid reliance on strategies with limited uptake in these groups, such as use of electronic portals. 27…”
Section: Discussionmentioning
confidence: 99%
“…The generalizability of our conclusions is also limited by the fact that most of the participants were well‐educated parents of children who were often quite ill. About 10% of families were excluded from the study due to lack of computer access or low English fluency. Some studies suggest that Internet based‐technologies may be problematic for people with linguistic challenges and those with lower education (Hartz et al ), whereas others have found that knowledge gained by such tools is not related to either education level, health literacy, or e‐health literacy (Yee et al ). Neither health literacy nor computer literacy was assessed in our study.…”
Section: Discussionmentioning
confidence: 99%